Pharmacist Allowances for the Dispensing of Emergency or Continuation of Therapy Prescription Refills and the COVID-19 Impact: A Multistate Legal Review - Nicholas DeRosa; Ka Leung; Julia Vlahopoulos; Joseph Lavino (University of Minnesota Libraries Publishing, 2021)
The COVID-19 pandemic has taught Americans many lessons, including what can happen when our healthcare system is strained. During the pandemic, certain healthcare related activities such as seeing or contacting a practitioner to receive a prescription refill may have been a challenge for some patients that could have interfered in the patient's medication adherence and continuity of care. Given these circumstances, the pandemic also shed light on the necessity for pharmacists to dispense emergency refills, which often is based on variable state pharmacy laws and regulations. State pharmacy laws and regulations vary from allowing pharmacists to dispense as much medication that is required for the patient to receive a new prescription to emergency refills being allowed only in the direst situations to save a patient's life. State pharmacy laws and regulations vary in the allowable quantities that may be dispensed, the federal schedule of controlled substance medications, and the circumstances they can be dispensed. In many cases, COVID-19 emergency regulations, governor executive orders and board of pharmacy guidance have expanded the authority for a pharmacist to dispense emergency refills. However, these allowances are often finite in nature and would end when the pandemic state of emergency ends. This paper seeks to analyze the laws and regulations in each state pertaining to the ability of a pharmacist to dispense an emergency refill when a patient's prescription does not have refills and provide a recommendation to optimize the state legal and regulatory landscape to expand current allowances.